Seventh Five-Year Plan 1985-90 Annual Plan 1985-86 Planning Department Punjab - Planning Commission (Planning Commission, 1985)
Before undertaking preparation of the Seventh Five year Plan, an exercise was conducted in the State as early as April, 1984 to identify the deficiencies which had accumulated up to the end of the Sixth Five Year Plan, while implementing various plan schemes, so that these deficiencies could be provided for systematically in the Seventh Plan. the main purpose of this exercise was to ensure that before embarking on new projects, a conscientious effort is made to consolidate the assets created so far.
Planning Department, Punjab